2017
DOI: 10.1177/0394632017694625
|View full text |Cite
|
Sign up to set email alerts
|

Extrathymic production of thymulin induced by oxidative stress, heat shock, apoptosis, or necrosis

Abstract: Thymic peptides are immune regulators produced mainly in the thymus. However, thymic peptides such as thymosin-α and thymopoietin have precursors widely expressed outside the thymus, localized in cell nuclei, and involved in vital nuclear functions. In stress-related conditions, they can relocalize. We hypothesized that another thymic peptide, thymulin, could be similarly produced by non-thymic cells during stress and have a precursor therein. Non-thymic cells, including macrophages and fibroblasts, were expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Danger/Damage Associated Molecular Patterns (DAMPs) are endogenous molecules derived from self, increased after cellular or oxidative stress [28], tissue damage [29], and stressor exposure [10, 30] and stimulate innate immunity and sterile inflammation. In most instances these self-molecules only function as DAMPs when they are in the extracellular environment due to stress-evoked release and/or necrotic cell death.…”
Section: Stimulation Of Stress-induced Sterile Inflammation: Dampsmentioning
confidence: 99%
“…Danger/Damage Associated Molecular Patterns (DAMPs) are endogenous molecules derived from self, increased after cellular or oxidative stress [28], tissue damage [29], and stressor exposure [10, 30] and stimulate innate immunity and sterile inflammation. In most instances these self-molecules only function as DAMPs when they are in the extracellular environment due to stress-evoked release and/or necrotic cell death.…”
Section: Stimulation Of Stress-induced Sterile Inflammation: Dampsmentioning
confidence: 99%
“…24 Furthermore, our recent study showed a role of thymulin in developing a fast response against oxidative stress in a damage-associated molecular pattern (DAMP)-like manner, restraining the inflammatory reaction. 25 Administration of STZ causes a sharp increase in the expression of JNK, which is considered a crucial factor in the STZ-induced β-cells death. 26 The JNK pathway is also involved in pathogenesis of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Furthermore, our recent study showed a role of thymulin in developing a fast response against oxidative stress in a damage-associated molecular pattern (DAMP)-like manner, restraining the inflammatory reaction. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Ironically, virtually nothing is known still about the molecular targets of one of the main secretory products of the thymus, i.e. thymulin, and about the mechanisms of its production [39], although almost half a century has passed since thymulin had been discovered. However, numerous interrelationships between thymus secretory products, including thymulin, and the components of the immunoneuroendocrine system are known [27].…”
Section: Discussionmentioning
confidence: 99%